Substance use disorders and COVID-19: reflections on international research and practice changes during the “poly-crisis” - Carver, Hannah; Ciolompea, Teodora; Conway, Anna; Kilian, Carolin; McDonald, Rebecca; Meksi, Andia; Wojnar, Marcin (Frontiers in Public Health, 2023)
Since March 2020, the COVID-19 pandemic has had a disproportionately high toll on vulnerable populations, coinciding with increased prevalence of alcohol-and drug-related deaths and pre-existing societal issues such as rising income inequality and homelessness. This poly-crisis has posed unique challenges to service delivery for people with substance use disorders, and innovative approaches have emerged. In this Perspectives paper we reflect on the poly-crisis and the changes to research and practice for those experiencing substance use disorders, following work undertaken as part of the InterGLAM project (part of the 2022. Lisbon Addictions conference). The authors, who were part of an InterGLAM working group, identified a range of creative and novel responses by gathering information from conference attendees about COVID-19-related changes to substance use disorder treatment in their countries. In this paper we describe these responses across a range of countries, focusing on changes to telehealth, provision of medications for opioid use disorder and alcohol harm reduction, as well as changes to how research was conducted. Implications include better equity in access to technology and secure data systems; increased prescribed safer supply in countries where this currently does not exist; flexible provision of medication for opioid use disorder; scale up of alcohol harm reduction for people with alcohol use disorders; greater involvement of people with lived/living experience in research; and additional support for research in low- and middle-income countries. The COVID-19 pandemic has changed the addictions field and there are lessons for ongoing and emerging crises.